Invective, mockery, obscenity: the ritual origins of ancient iambography (Circe de clásicos y modernos, 2018)
Iambic poetry in Ancient Greek often dates back to communal celebrations and religious rituals traced to the cults of Demeter and Dionysus. These events coincide with the Iambus, mainly featuring invective, insulting and obscene language. The present work intends to precisely look into some testimonies relating to different ceremonies of these two deities that, although late and indirectly passed on, they allow us to pick up again the threads between cultural songs and literary iambus. In fact, as can be inferred from them, it is possible to draw a continuity line between the religious and cultural context of the Eleusinian and Dionysian festivities in the archaic Greek world and the specifically literary iambic compositions that emerged around the 7th century BC. We will focus on certain Iambus of the famous poets Archilochus of Paros and Hipponax of Ephesus, which, to our knowledge, are reflections of those ancient ritual songs.
Keywords: Iambic poetry; invective; aeschrology; Archilochus; Hipponax